The Effect of Emotional Intelligence Training Based on Social Support Theory on Reducing Perceived Stress and Promoting Communication Skills among Male High School Students in Hamadan - Narges Nouri; Babak Moeini; Ali Ghaleiha; Javad Faradmal; Iraj Zareban (Hamadan University of Medical Sciences, 2017)
Background and Objectives: Research has shown that 80% of people's success is associated with emotional intelligence-related skills. Accordingly, the aim of this study was to evaluate the effect of emotional intelligence training based on social support theory on assuaging perceived stress and promoting communication skills among male high school students of Hamadan, Iran. Materials and Methods: In this experimental study, 100 male high school students in Hamadan, Iran, were randomly assigned to experimental and control groups (n=50 students in each group). The data collection tools included the Social Support Scale, Schutte Self-Report Emotional Intelligence Test, Burton's Communication Skills, and Cohen's Perceived Stress Scale. The intervention included five sessions for students and two sessions for parents and school teachers, which was performed for one month in the experimental group. The experimental and control groups were separately followed up one and two months after the intervention. Data were analyzed with SPSS, version 16 and, using Chi-square test, paired t-test, and repeated measures analysis of variance. Results: The results revealed significant differences between the mean scores of the two groups regarding the theoretical constructs of social support, emotional intelligence, communication skills, and perceived stress (P<0.05). Conclusions: Emotional intelligence training based on social support was effective in reducing stress and promoting communication skills of students; therefore, the use of this theoretical framework for designing and evaluating educational interventions is suggested.